Choosing preclinical study models of diabetic retinopathy: key problems for consideration - Mi XS; Yuan TF; Ding Y; Zhong JX; So KF (Dove Medical Press, 2014)
Xue-Song Mi,1,2 Ti-Fei Yuan,3,4 Yong Ding,1 Jing-Xiang Zhong,1 Kwok-Fai So4,5 1Department of Ophthalmology, First Affiliated Hospital of Jinan University, Guangzhou, Guangdong, People’s Republic of China; 2Department of Anatomy, Li Ka Shing Faculty of Medicine, The University of Hong Kong, Hong Kong, People’s Republic of China; 3School of Psychology, Nanjing Normal University, Nanjing, People’s Republic of China; 4Department of Ophthalmology, Li Ka Shing Faculty of Medicine, The University of Hong Kong, Hong Kong; 5Guangdong-Hongkong-Macau Institute of Central Nervous System, Jinan University, Guangzhou, People’s Republic of China Abstract: Diabetic retinopathy (DR) is the most common complication of diabetes mellitus in the eye. Although the clinical treatment for DR has already developed to a relative high level, there are still many urgent problems that need to be investigated in clinical and basic science. Currently, many in vivo animal models and in vitro culture systems have been applied to solve these problems. Many approaches have also been used to establish different DR models. However, till now, there has not been a single study model that can clearly and exactly mimic the developmental process of the human DR. Choosing the suitable model is important, not only for achieving our research goals smoothly, but also, to better match with different experimental proposals in the study. In this review, key problems for consideration in choosing study models of DR are discussed. These problems relate to clinical relevance, different approaches for establishing models, and choice of different species of animals as well as of the specific in vitro culture systems. Attending to these considerations will deepen the understanding on current study models and optimize the experimental design for the final goal of preventing DR. Keywords: animal model, in vitro culture, ex vivo culture, neurovascular dysfunction